(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Moullava spicata (Dalz) Nicolson is an effective therapeutic plant of the Western Ghat forests of India. Using Hydroacetonic Moullava spicata leaf extract (MsLE) as a novel environmentally benign resource for the green synthesis of AgNPs. Synthesized Moullava spicata leaf extract silver nanoparticles (MsLE-AgNPs) were explored for antioxidant and anticancer activity. The development of a brownish color in the reaction mixture signified the AgNPs synthesis. The spectroscopic analysis of synthesized MsLE-AgNPs were accomplished through UV-visible spectrophotometer, Fourier transform infrared (FTIR) spectroscopy, powder X-ray diffraction (XRD), High-resolution transmission electron microscopy (HR-TEM), and Dynamic light scattering (DLS). The antioxidant potentiality was done by total phenolic content (TPC), total flavonoid content (TFC), and DPPH assay. Anticancer potentiality was evaluated by MTT assay against Human bone marrow neuroblastoma (SH-SY5Y) cancer cell lines and induction of apoptosis was checked in SH-SY5Y cells. The absorption maxima of AgNPs at 405 nm was validated by UV-vis spectroscopy. FTIR demonstrated the contribution of chemical groups in both the reduction and stabilization process of AgNPs. Powder XRD patterns validated crystallinity. HR-TEM images showed spherical-shaped and ⁓10-20 nm sized AgNPs. The zeta potential of -28.4 mV and 68.6 nm hydrodynamic size of MsLE-AgNPs was confirmed by the DLS spectrum. The TPC and TFC were 134.76±0.096mg GAE/100mL and 32.38±0.12μg QE/mL respectively. Dose-dependent DPPH radical scavenging assay showed a 95.89±0.016% inhibition. In MTT assay MsLE-AgNPs exhibited 13.88±0.015% cell viability and induced 74.68% apoptosis in cancer cells. The current results confirmed the potentiality of MsLE-AgNPs for antioxidant and anticancer applications.